Parametric Study of Spar Platform Responses - Motimbun, Nony Motimbun (2010)
Since the first spar platform was installed in Gulf of Mexico (GOM) in 1996, spar platform has been regarded as competitive floating structure for deep-sea oil exploration. In this study, dynamic analysis is applied to measure the responses of a typical spar platform in order to measure instantaneous amplitude and frequency fluctuations of three degrees freedom (surge, heave and pitch). The analysis was performed for a spar subjected to random wave loading represent an operational condition of 100-year storm in Gulf of Mexico. The first part of this project focuses on the detailed information of the chosen existing spar. Next, the evaluation of the responses using mathematical calculations and it is modeled as a rigid body connected to the sea floor by multi component catenaries mooring lines. Frequency domain analysis has been performed by choosing P-M Spectrum model to represent an appropriate density distribution of seawater at the site under consideration. The parameters chosen for assessing the responses are the stiffness that varies t 10% of original stiffness and different condition of hydrodynamic coefficients (Clean and Fouled). From the analysis, the response increases when the stiffness was lower and decreased when the stiffness is higher than the original. The smaller value of hydrodynamic coefficient affects the spar motion by decreasing it. The results presented in this paper will provide an insight to the differences in Spar motion responses due to the variation in both design parameters. The findings should be beneficial for spar design in an early project stage.